1997
DOI: 10.1089/dna.1997.16.323
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Type I Receptor Activation Promotes Cerebellar Neuron Survival Through the cAMP/PKA Signaling Pathway

Abstract: The molecular nature, transduction pathways, and neurotrophic functions of pituitary adenylate cyclase activating peptide (PACAP) receptors were studied in primary culture of rat cerebellar granule cells. We show that cerebellar neurons express several PACAP type I receptor (PVR I) isoforms, including the short (PVR Is) and the Hop (PVR I-Hop) splice variants, the latter being restricted to neurons and not found in cerebellar glial cell cultures. In vitro, cerebellar granule cells die rapidly in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 26 publications
3
54
0
Order By: Relevance
“…The ␣IR3 mouse monoclonal antibody against IGF-1R specifically recognizes the extracellular ␣-subunit of IGF-1R and inhibits its ligand-mediated effects (Kienlen Campard et al, 1997). We found that ␣IR3 had no effect on baclofen-induced IGF-1R phosphorylation (Fig.…”
Section: Gaba B Receptor Activation Induces Igf-1r Transactivationmentioning
confidence: 71%
“…The ␣IR3 mouse monoclonal antibody against IGF-1R specifically recognizes the extracellular ␣-subunit of IGF-1R and inhibits its ligand-mediated effects (Kienlen Campard et al, 1997). We found that ␣IR3 had no effect on baclofen-induced IGF-1R phosphorylation (Fig.…”
Section: Gaba B Receptor Activation Induces Igf-1r Transactivationmentioning
confidence: 71%
“…Collectively, these data indicate that caspase-6 may mediate ethanol-induced activation of caspase-3. The neuroprotective effects of PACAP on granule neurons are primarily mediated through the cAMP͞protein kinase A signaling cascade (16,23,24,39). Because the inhibitory effect of PACAP on caspase-3 activity is mediated through the protein kinase A pathway (17), it is possible that inactivation of caspase-6 by PACAP can be ascribed to a protein kinase A-dependent phosphorylation (40).…”
Section: Effects Of Pacap On Ethanol-induced Granule Cell Apoptosismentioning
confidence: 99%
“…The anti-apoptotic effects of cAMP are seen in many types of neuronal systems, including cerebellar granule neurons [164][165][166][167][168][169], dopamine neurons [170], septal cholinergic neurons [171], and sympathetic and sensory neurons [172][173][174]. A clinical study on POAG patients treated with a food supplement containing forskolin and rutin (Kronek®) has shown an improvement of the electrophysiological activity of RGC as measured by PERG analysis [175,176].…”
Section: Glutamate Modulationmentioning
confidence: 99%